THE EFFECT OF BRAND EQUITY AND PRODCUT QUALITY TOWARD CONSUMER’S PURCHASE DECISION (CASE STUDY: J.CO DONUTS & COFFEE MANADO) - Kiling, Christika; Tumewu, Ferdinand F. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract : Purchasing decisions are in the stage of the buyer decision-making process in which consumer actually buy. Some of the factors that influence consumer purchase decisions are brand equity and product quality. This research aimed to analyze simultaneously and partially effect of brand equity and product quality toward consumer purchase decision of J.CO Donuts & Coffee Manado. Theories supporting research are brand equity, product quality and purchase decision. The population refers to J.CO Donuts & Coffee customers in Manado city with sample size as many as 100 respondents. This research used quantitative analysis and the data analysis technique used is multiple regression analysis. The result showed that simultaneous brand equity and product quality significantly influence consumer purchasing decision. Partially brand equity and product quality are significantly influence consumer purchase decision. Brand equity and product quality has contributed greatly to the consumer purchase decision, then the parties should consider factors J.CO brand equity and product quality in company. Keywords: Brand Equity, Product Quality, Purchase Decision.